O jogo da distinção: C. A. Paulistano e Fluminense F. C.: um estudo da construção das identidades clubísticas durante a fase amadora do futebol em São Paulo e no Rio de Janeiro (1901-1933) - Fernandez, Renato Lanna (2016)
This work investigates the process of club identities formation during the Brazilian football amateur stage (1900 – 1933), focusing on the cases of C A Paulistano and Fluminense F. C.. This identity construction process usually gives these clubs the mark of elitization based on distinction and refinement. By deepening and qualifying this version consecrated by sport memorialism, it is hereby intended to analyze the history of these two clubs, during the initial years of development of football in Rio de Janeiro and in São Paulo, highlighting the relation between the sport and the development of the two cities. In order to demonstrate our central argument, we will bring up social, economic, political and cultural aspects that can be considered fundamental in the construction of the image of distinction attributed both to Fluminense and to Paulistano. Employing the comparative method, we will try to point the similarities and differences in the history of the clubs, assuming as theoretical basis the works of Bourdieu on distinction, of Hobsbawm and Ranger on the invention of traditions and of Halbwachs on collective memory. Together with the documental archives from both analyzed institutions, we will use as sources the documentation produced by the clubs and periodicals from the period. We seek to demonstrate, through the memorial reports produced by writers, managers and former athletes, the perpetration of a range of symbolic values and traditions that associated the Paulistano and the Fluminense to a space of distinction and refinement that reproduced throughout the generations and that remains in the sport imaginary until today.